Digital, from emergency to tool at the service of the teacher to promote learning - Ferraro, Speranzina (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The hospital school has a long history in our country, which has led to its gradual incorporation in all paediatric hospitals, becoming an important stage in each patient's treatment plan. Born quietly in the 1950s, it finally entered into the ordinariness of our school system with CM n. 353/1998 and was institutionalised first in the large metropolitan paediatric hospitals and then in all the regions. Its value as a school to all intents and purposes is recognised, a guarantee of the right to education for everyone and, above all, its capacity to promote the wellbeing and growth of the person, even in difficult situations (Ferraro, 2012:50-56).